On the status and validity of the recently described Raorchestes kollimalai Gowande, Ganesh & Mirza 2020 - Narayanan, Surya; Suyesh, Robin; Das, Sandeep (Zootaxa, 2021)
A recent addition to the Indian herpetofauna is Roarchestes kollimalai Gowande, Ganesh & Mirza 2020, a bush frog species, described based on a type series of three specimens from the Kolli hills in the lesser-known Eastern Ghats of Tamil Nadu, India (Gowande et al. 2020). The authors attempted to resolve the status of the previously ambiguously identified R. cf. leucolatus from this region (Ganesh & Arumugam 2016) through an integrated approach using morphology, molecular DNA and call acoustics. Gowande et al. (2020) described the new species based on their morphology, biogeographic and acoustic data, for a shallow divergent lineage differing with 1.2–1.9% in the mitochondrial 16S gene from a closely related species R. charius. After a thorough reading of Gowande et al. (2020), we found serious flaws in the publication, as the authors overlooked many errors and misrepresented their own data, leaving their new taxon questionable with respect to its validity and status. In this work, despite pointing out these errors made by the authors, we also discuss the validity of their new taxon based on their results and suggest the way forward to resolving the issue.